Magnesium-Coordinated Chelation Control in 1,3-Dipolar Cycloaddition of Chiral α-Alkoxymethyl Ether Nitrile Oxide: Application to the Synthesis of (–)/(–)-cis-Clausenamide - Tanda, Kazuhiro; Toyao, Atsushi; Watanabe, Akiko; Sakamoto, Masanori; Yamasaki, Tetsuo (Synlett, 2014)
A facile regio- and diastereoselective nitrile oxide cycloaddition method using magnesium-coordinated chelation control of chiral α-alkoxymethyl ether nitrile oxide is reported. This reaction could be successfully applied as a key step in both the formal total synthesis of (–)-clausenamide and the total synthesis of (–)-cis-clausenamide.
Keywords: cycloaddition; magnesium; nitrile oxide; diastereoselectivity; natural products